Revising the History of Nitchevo with Text Archives - Podhajecka, Mirosława (Studia Anglica Posnaniensia, 2023)
This article focuses on the way nitchevo, a nineteenth-century Russian borrowing, was adopted into the English language. In order to investigate the history of the word, six digital text archives were considered. The results of the research are promising: not only do they allow one to trace antedatings for both senses, which updates the treatment of nitchevo in the Oxford English Dictionary (OED), but they also shed light on its semantic development, spelling variation, and route of transmission. Tellingly, albeit unsurprisingly, the evidence suggests that the press is responsible for boosting the recognition of the word on both sides of the Atlantic. All this indicates that the potential of modern research tools, including British and American newspaper archives, remains to be fully explored.